Radiation Protection Knowledge, Attitudes, and Practices Among Fluoroscopy-Utilizing Doctors at Misurata Medical Centre, Libya. - Mohamed Sherfad; Mohamed Shaka; Omar Alhaddad (AlQalam Journal of Medical and Applied Sciences, 2024)
The aim of this study is to study the level of knowledge, attitude and practice among medical staff in Misurata medical centre using C-arm unit in operating theatre. A cross-sectional study of doctors in Misurata medical centre were carried out using a questionnaire distributed to doctors in various specialties using C-arm unit in the operation theatre. The questionnaire composed of 20 questions containing questions about general data (age, gender, marital state, specialty and years of experience), 5 questions about basic radiation protection knowledge, 3 questions about attitude and 6 questions about practice. 177 questionnaires were sent and 126 were recollected, the results filled out in Microsoft Excel and analysed using SPSS. A significant knowledge gap was identified among participants (n=112), with the majority lacking knowledge of radiation protection principles. Attitudes towards radiation protection measures varied, with a significant proportion of respondents recognizing the harm of using C-arm radiation without protection. Practice patterns showed significant proportion of unsafe practice. The study reveals significant knowledge gaps, suboptimal attitudes, and unsafe practice among non-radiology physicians using the fluoroscopy unit. Targeted educational intervention, increased availability of radiation protection equipment, and standardized protocols will improve these results and minimizing the risks associated with radiation exposure to both healthcare providers and patients. الهدف من هذه الدراسة هو دراسة مستوى المعرفة والسلوك والممارسة بين الاطقم الطبية في مركز مصراتة الطبي باستخدام وحدة الاشعة بالعمليات. أجريت دراسة مقطعية للأطباء في المركز الطبي مصراتة باستخدام استبانة وزعت على الأطباء في مختلف التخصصات التي تستخدم وحدة C-arm في غرفة العمليات. تتكون الاستبانة من 20 سؤالا تشمل أسئلة حول البيانات العامة (العمر والجنس والحالة الاجتماعية والتخصص وسنوات الخبرة)، و 5 أسئلة حول المعرفة الأساسية للوقاية من الإشعاع، و 3 أسئلة حول السلوك و 6 أسئلة حول الممارسة. . تم إرسال 177 استبانة وتم جمع 126 استبانة ، ومن ثم تم ملء النتائج في Microsoft Excel وتحليلها باستخدام برنامج SPSS. تم تحديد فجوة معرفية كبيرة بين المشاركين (n=112)، حيث أن الغالبية تفتقر إلى المعرفة بمبادئ الوقاية من الإشعاع. وتفاوتت المواقف والسلوكيات تجاه تدابير الوقاية من الإشعاع بين المشاركين، حيث بينت نسبة كبيرة من المجيبين ادراكها بالضرر الناجم عن استخدام الاشعة الناتجة من استخدام جهاز (C-arm) في عدم وجود وقاية من الاشعة. كما أظهرت أنماط الممارسة نسبة كبيرة من الممارسات غير الآمنة. كشفت الدراسة عن فجوات معرفية كبيرة، وسلوكيات دون المستوى الأمثل، وممارسة غير آمنة بين الأطباء غير المتخصصين في الأشعة الذين يستخدمون وحدة التنظير الفلوري. ستؤدي التدخلات التعليمية المستهدفة وزيادة توفر معدات الوقاية من الأشعة وتوحيد البروتوكولات إلى تحسين هذه النتائج وتقليل المخاطر المرتبطة بالتعرض للإشعاع لكل من مقدمي الرعاية الصحية والمرضى